Age-related decline in aerobic potential in trained to well-trained cyclists - Hyttel, M. K.; Kristiansen, M. V.; Hansen, E. A. (Journal of Science and Cycling, 2022)
It is generally considered that an age-related decline in aerobic capacity occurs as we get older. The decline has been described to be approximately 1% per year in adult men and women, starting from the age of about 25 years. It may, however, be influenced by the activity level of the individual [1]. The aim of the present study was therefore to examine the effect of aging on aerobic potential in trained to well-trained cyclists, in a cross-sectional study.